Lethal Effects of Toxic Plants (Neem, Datura, Acanthus) on Artemia Species - Jihad, T. A.; Bhuyan, M. S.; Islam, M. S. (Journal of Scientific Research, 2019)
Effects of the water-soluble extracts (dry leaf powder of Azadirachta indica, Datura stramonium and Acanthus ilicifolius) were studied on the behavioral pattern and mortality of Artemia species. The extracts of all the plants brought significant change in the behavioral pattern of Artemia. The Artemia become agitated just offer exposure to the extract and started to move upwards and downwards vigorously. The Artemia exposed to the various concentration of water-soluble plant extracts were unable to maintain dorso-ventral position and dropped to the bottom finally. The mortality rates recorded after 24 h exposure to the extract Azadirachta indica were 30% at 1500 mg/L and 70% at 3000 mg/L. Similarly, after 24 h exposure to the extracts of Datura stremonium, the mortality rates were 40% at 2000 mg/L and 75% at 3500 mg/L. Again, after 24 h has exposure to the extracts of Acanthus ilicifolius, the mortality rates were 35% at 2500 mg/L and rose to 80% at 4000 mg/L. The 24 h LC50 values of the water-soluble extracts of Neem, Datura and Acanthus were 2331.930, 2357.948 and 2922.957. Artemia was more sensitive to the water-soluble extract of Neem than Datura and Acanthus.